2021
DOI: 10.1371/journal.pone.0253878
|View full text |Cite
|
Sign up to set email alerts
|

Stress amelioration response of glycine betaine and Arbuscular mycorrhizal fungi in sorghum under Cr toxicity

Abstract: Chromium toxicity is a major problem in agricultural soils that negatively affects a plant’s metabolic activities. It reduces biochemical and antioxidant defence system’s activities. In search of the solution to this problem a two-year pot experiment (completely randomized design with three replications), in three genetically different varieties of sorghum (SSG 59–3, HJ 513 and HJ 541) under Cr toxicity (2 and 4 ppm) was conducted to determine the effect of glycine betaine (50 and 100mM) and Arbuscular mycorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 63 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In salt-stressed sorghum, reductions were observed in MDA content, polyphenol oxidase (PPO) activity, and H 2 O 2 when treated with GB. However, Cr stress increased the liberation of ROS and intermediate products (OH − and H 2 O 2 ), which enhances the activity of PPO and MDA content in sorghum [173].…”
Section: Ros Scavenging By Non-enzymatic Antioxidantsmentioning
confidence: 95%
“…In salt-stressed sorghum, reductions were observed in MDA content, polyphenol oxidase (PPO) activity, and H 2 O 2 when treated with GB. However, Cr stress increased the liberation of ROS and intermediate products (OH − and H 2 O 2 ), which enhances the activity of PPO and MDA content in sorghum [173].…”
Section: Ros Scavenging By Non-enzymatic Antioxidantsmentioning
confidence: 95%
“…However, this type of approach might be useful for efficiently controlling plant diseases by exposing crop species to the appropriate active gas composition for the type of disease. Recently, Kumar and co-workers reported that glycine betaine and Arbuscular mycorrhizal fungi treatment reduces chromium toxicity via reduction of oxidative stress [55][56][57]. Combining such treatments with N 2 O 5 gas exposure may allow for the development of more effective and harmless disease control methods.…”
Section: Plos Onementioning
confidence: 99%
“…Glycine betaine is reported to alleviate numerous abiotic stresses in sorghum ( Kumar, 2021 ). The present study revealed that HZRP treatment alleviated Cr toxicity in V. radiata seedlings.…”
Section: Discussionmentioning
confidence: 99%